Knowledge and participation in mass drug administration against lymphatic filariasis and soil-transmitted helminth infections among the community members in Dar es Salaam, Tanzania. (23rd December 2022) - Ngunyali, Diana A; Mpomele, Stella S; Kilonzi, Manase; Mutagonda, Ritah F; Mikomangwa, Wigilya P; Mlyuka, Hamu J; Kibanga, Wema; Marealle, Alphonce Ignace
ABSTRACT: Background: Although the WHO has made an effort to ensure optimal participation of the community in mass drug administration (MDA) against lymphatic filariasis (LF) and soil-transmitted helminth infections (STHIs), studies are still reporting suboptimal coverage. This study assessed the knowledge and participation of the community in MDA against LF and SHTIs in Tanzania to provide updates on its acceptability. Methods: A cross-sectional study was conducted in Dar es Salaam from December 2021 to February 2022 among market vendors. The information regarding demographic characteristics, knowledge and participation in MDA was collected using a questionnaire. Statistical Package for Social science version 26 was used for data analysis. Results: More than half of the participants demonstrated an adequate level of knowledge of LF and STHI, 212 (50.8%) and 267 (64%), respectively. Only 286 (68.5%) reported having heard about MDA against LF and STHIs, out of which 119 (42%) had taken the medication. Of those who disagreed to participate in MDA, 20 (50%) claimed to fear the side effects of the medication. Conclusions: This study found that the community has average knowledge and poor participation in MDA against LF and STHIs. Community sensitization is recommended to increase the participation of the community.